10 The role of impaired myocardial microvascular function dysglycaemic patients with heart failure. (1st November 2021) - Brown, LAE; Wahab, A; Klassen, J; Saunderson, CED; Das, A; Craven, T; Chowdhary, A; Jex, N; Levelt, E; Xue, H; Kellman, P; Greenwood, JP; et al.
Abstract : Background: Dysglycaemic (either diabetic or prediabetic) heart failure patients have worse outcomes than normoglycaemic heart failure patients. It is possible to quantify occult ischaemic heart disease (IHD, either ischaemia on stress perfusion or infarction on late gadolinium enhancement) and myocardial microvascular function (by quantitative perfusion). We aimed to investigate whether excess risk in dysglycaemic patients with heart failure is mediated by occult ischaemic heart disease or myocardial microvascular dysfunction. Methods: We recruited outpatients with a recent diagnosis of heart failure (LVEF < 50% on echocardiogram). Exclusion criteria included known previous myocardial infarction, revascularisation or angina. Patients were defined as dysglycaemic if they had a previous diagnosis of diabetes or HbA1c>42 mmol/mol. Patients were followed up for major adverse cardiovascular events (MACE) including cardiovascular death, heart failure hospitalisation, non-fatal MI and non-fatal stroke. CMR studies were performed on a Siemens Prisma 3T scanner (Siemens Healthineers, Erlangen, Germany). Results: Of 343 patients, 176 were normoglycaemic and 167 dysglycaemic. During follow up (median 623 days) there were 35 MACE events in 30 patients, including 23 heart failure hospitalisations (6.7%), 4 strokes (1.1%), 7 cardiovascular deaths (2.0%) and 1 (0.3%) acute coronary syndrome. Univariate Cox regression analysis showed left ventricle ejection fraction (LVEF), right ventricle ejection fraction (RVEF), native T1, extracellular volume fraction, myocardial perfusion reserve (MPR) and the presence of occult IHD all to have significant association with MACE. However MPR was only associated with MACE in dysglycaemic patients (hazard ratio (HR) 0.19, 95% confidence interval (CI) 0.08–0.46, P<0.001) and occult IHD was only associated with MACE in normoglycaemic patients (HR 3.45, 95% CI 1.23–9.71, P=0.02) ( figure 1 ). The relationship between MPR and MACE in dysglycaemic patients was still significant even after correction for LVEF, RVEF and HbA1c (HR 0.553, 95% CI 0.318–0.962, P=0.036). Conclusions: In patients with a recent diagnosis of heart failure, impairment of myocardial microvascular function is associated with adverse outcomes in dysglycaemic but not normoglycaemic patients, possibly explaining the excess risk in these patients. Further studies are needed to confirm these findings and establish if impaired microvascular function or associated outcomes can be altered by medical therapy.